Efficient biallelic knock-in in mouse embryonic stem cells by in vivo-linearization of donor and transient inhibition of DNA polymerase θ/DNA-PK - Daisuke Arai (Nature Portfolio, 2021)
Abstract CRISPR/Cas9-mediated homology-directed repair (HDR) is used for error-free targeted knock-in of foreign donor DNA. However, the low efficiency of HDR-mediated knock-in hinders establishment of knock-in clones. Double-strand breaks (DSBs) induced by CRISPR/Cas9 are preferentially repaired by non-homologous end joining (NHEJ) or microhomology-mediated end joining (MMEJ) before HDR can occur, thereby preventing HDR-mediated knock-in. NHEJ/MMEJ also cause random integrations, which give rise to false-positive knock-in events, or silently disrupt the genome. In this study, we optimized an HDR-mediated knock-in method for mouse embryonic stem cells (mESCs). We succeeded in improving efficiency of HDR-mediated knock-in of a plasmid donor while almost completely suppressing NHEJ/MMEJ-based integration by combining in vivo-linearization of the donor plasmid, transient knockdown of DNA polymerase θ, and chemical inhibition of DNA-dependent protein kinase (DNA-PK) by M3814. This method also dramatically improved the efficiency of biallelic knock-in; at the Rosa26a locus, 95% of HDR-mediated knock-in clones were biallelic. We designate this method BiPoD (Biallelic knock-in assisted by Pol θ and DNA-PK inhibition). BiPoD achieved simultaneous efficient biallelic knock-in into two loci. BiPoD, therefore, enables rapid and easy establishment of biallelic knock-in mESC lines.